The role of visual aids in the clinical success of posterior restorations: Randomized controlled clinical trial - İpek Çubukcu; Merve İşcan Yapar (Heliyon)
Objective: This clinical study aimed to assess the impact of utilizing loupes and dental operating microscopes (DOM) with varying magnifications on the success of class II direct composite restorations. Methods: A total of 130 class II, moderately deep caries teeth from 85 patients were randomly assigned to four groups: naked eye, ×3 loupe, ×5 loupe, and ×8.5 DOM. Cavities were restored with or without magnification. The restorations were evaluated according to World Dental Federation criteria at 1, 6, and 12-month intervals by previously calibrated evaluators. Cochran's Q test was used to compare paired scores across three or more time points within groups, while the Friedman test was employed to compare scores at three or more time points. Multiple comparisons were adjusted using the Bonferroni correction. The significance level was set at p < 0.05. Results: Statistical analysis revealed no significant differences among the groups at the 1-, 6-, and 12-month follow-up periods (p > 0.05). Although not statistically significant, the magnified groups exhibited higher scores in aesthetic anatomical form, proximal form, postoperative sensitivity, periodontal response, and adjacent mucosalcriteria compared to the naked eye group. Conclusion: Although no statistically significant difference was observed at the 12-month follow-up between restorations performed with and without magnification, the groups using magnification showed higher scores.